2006
DOI: 10.1017/s0144686x05004502
|View full text |Cite
|
Sign up to set email alerts
|

Filial norms and family support in a comparative cross-national context: evidence from the OASIS study

Abstract: The article aims to answer three questions: How strong are the bonds of obligations and expectations between generations? To what extent are different types of support exchanged between generations? What are the impacts of filial norms, opportunity structures and emotional bonds on the exchange of inter-generational support between adult children and older parents across societies? It reports findings from the five-country (Norway, England, Germany, Spain and Israel) OASIS study, which collected data from repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
167
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 39 publications
7
167
1
7
Order By: Relevance
“…One of the most basic social norms concerns mutual help within families (family solidarity). Filial norms are the basis for support from adult children to their ageing parents (Lowenstein and Daatland 2006). Hence, these norms are an important basis for social integration of older people.…”
Section: Cultural Norms As Reference System For Individual Expectationsmentioning
confidence: 99%
“…One of the most basic social norms concerns mutual help within families (family solidarity). Filial norms are the basis for support from adult children to their ageing parents (Lowenstein and Daatland 2006). Hence, these norms are an important basis for social integration of older people.…”
Section: Cultural Norms As Reference System For Individual Expectationsmentioning
confidence: 99%
“…We have always tried that they were well served. As OASIS Project concluded, normative beliefs are sufficiently flexible to adapt to new social realities such as gender equality and increased female participation in paidwork (Lowenstein and Daatland 2006). There are different ways in which filial norms are translated into emotional and instrumental support and help.…”
mentioning
confidence: 99%
“…The strong normative component of inter-generational solidarity has made individual goals and personal decisions (including those related to care) often dependent on perceived family expectations (Lowenstein and Daatland, 2006). Comparative studies have shown that the family protection plays a more important role in Spain than in other European countries, with members of the family network seeing help more as a social duty than as an option (Katz et al, 2010; Reis.…”
Section: Conditioning Factors Of the Preferences In Caringmentioning
confidence: 99%